Can Graphic Organisers Enhance Science Achievement in School Students? - Balamurugan, M. (SCHOOL SCIENCE, 2020)
Graphic organisers are teaching and learning tools that show the organisation of concepts as well as relationships between them in visual formats. The objective of the study was to find out the effectiveness of graphic organisers on science achievement. In this study, three groups pre-post test experimental design was adopted. Ten mini-lessons on the graphic organiser were conducted for the experimental group for 12 days. Science achievement test with four multiple-choice options was used. A total of 75 students was selected and divided into three groups of 25 each, viz., control, module, and experimental based on the group mean of the pretest. The t value calculated between the pre-test and post-test mean of the module group was found to be significant (5.97) and the effect size was found to be very large (1.716). The t value calculated between the pre-test and post-test mean of the experimental group was found to be significant (21.64) and the effect size was found to be huge (4.866). Today, most of the concepts are overlapping and need multiple perspectives to understand but through graphic organisers, students can prepare visual representations that can be used for remembering, clarifying, and easily relating to multiple aspects of the concepts